New data on the chronology of the Vale do Forno sedimentary sequence (Lower Tejo River terrace staircase) and its relevance as a fluvial archive of the Middle Pleistocene in western Iberia. (15th June 2017) - Cunha, Pedro P.; Martins, António A.; Buylaert, Jan-Pieter; Murray, Andrew S.; Raposo, Luis; Mozzi, Paolo; Stokes, Martin
Abstract: The Vale do Forno archaeological sites (Alpiarça, central Portugal) document the earliest human occupation in the Lower Tejo River, well established in geomorphological and environmental terms, within the Middle Pleistocene. In a staircase of six fluvial terraces, the Palaeolithic sites were found on the T4 terrace (+24 m, above river bed) which is made of a basal Lower Gravels unit (LG) and an overlying Upper Sands unit (US). Geomorphological mapping, coupled with lithostratigraphy, sedimentology and luminescence dating (quartz-OSL and K-feldspar post-IRIR290 ) were used in this study. The oldest artefacts found in the LG unit show crude bifacial forms that can be attributed to the Acheulian. In contrast, the US unit has archaeological sites stratigraphically documenting successive phases of an evolved Acheulian. Luminescence dating and correlation with the Marine Isotopic Stages suggest that the LG unit has a probable age of ca. 335 to 325 ka and the US unit an age of ca. 325 to 155 ka. This is in contrast to previous interpretations ascribing this terrace (and lithic industries) to the Last Interglacial and early phases of the Last Glacial. The VF3 site (Milharós), containing Micoquian (Final Acheulian) industries (with fine and elaborated bifaces), found in a stratigraphic level located between the T4 terrace deposits and a colluvium associated with Late Pleistocene aeolian sands, is younger than 155 ka but much older than 32 ka. Highlights: Re-analysis of the Vale do Forno archaeology sites, Lower Tejo River, Portugal. Evidence for Palaeolithic human occupation derived from the T4 river terrace. Artefacts from Lower Gravels unit to Upper Sands unit reveal evolving Acheulian industry. New OSL dates suggests Lower Gravels unit to Upper Sands unit time periods span 335–325 and 325–155 ka. Suggests human occupation is older than the initial Late Pleistocene interpretation.